2016
DOI: 10.3153/jfhs16016
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Microwave, Autoclave and Hot Air Oven Stabilized Wheat Bran Substitution on Nutritional and Sensorial Properties of Flat Breads

Abstract: Abstract:The influence of stabilized wheat bran enrichment on the nutritional and sensorial properties of leavened and unleavened flat bread was studied. Wheat bran was stabilized with three applications (hot air oven, microwave and autoclave). The stabilization methods affected the physical characteristics of bazlama (thickness, spread factor) and yufka (diameter, thickness, spread factor) samples. In bazlama samples, substitution of stabilized wheat bran (SWB) lead to significant decrease in L* and increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 42 publications
4
8
0
Order By: Relevance
“…Wherein, the HWB and HWG showed higher significant (P B 0.05) changes in crumb color values than UWB and UWG values, especially with the steady increase of their levels. These results are in agreement with the findings of of Ertaş (2016), Gajula (2017) and Wang et al (2017a, b). These changes in crumb color of FB loaves were due to the potential color of wheat germ and wheat bran and their fiber contents (Gómez et al 2012;Nandeesh et al 2011).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Wherein, the HWB and HWG showed higher significant (P B 0.05) changes in crumb color values than UWB and UWG values, especially with the steady increase of their levels. These results are in agreement with the findings of of Ertaş (2016), Gajula (2017) and Wang et al (2017a, b). These changes in crumb color of FB loaves were due to the potential color of wheat germ and wheat bran and their fiber contents (Gómez et al 2012;Nandeesh et al 2011).…”
Section: Resultssupporting
confidence: 93%
“…The increase in WA was due to the water absorption capacity of the hydrocolloids, globulin protein and fiber-rich fractions specifically, pentosans of wheat germ and wheat bran. During dough mixing, these components could compete with other dough components for water through hydrogen bonding; alter the dough WA (Cai et al 2014;Ertaş 2016). Our results showed that the WA of flour blends (FH 5-20 ) with HWB and HWG was lower than that of flour blends (FUH 5-20 ) with the UWB and UWG at the same conditions, but no significant difference (P B 0.05) was observed for most samples, as has already been observed by Wang et al (2017a, b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations